Spherical electric and magnetic phase with Heisenberg spherical ferromagnetic spin by some fractional solutions - Körpınar, Talat; Körpınar, Zeliha (Elsevier GmbH, 2021)
Physically, unit sphere S2 is illustrated to be a 2-sphere in space with a positive curvature. In this paper, we construct new characterization for spherical electric and magnetic flow density of spherical St?magnetic flows of particles by the spherical frame in S2 spherical space. Thus, we obtain some new optical conditions of spherical St?magnetic electric and magnetic phase by using spherical magnetic fields. Moreover, we determine spherical magnetic Lorentz flux for spherical vector fields. Finally, electric and magnetic phase of spherical surface are demonstrated in uniform magnetic surface by using the analytical and fractional numerical results. © 2021 Elsevier GmbH
Keywords: Heisenberg ferromagnetic spin; Spherical electric and magnetic flow density; Spherical frame; Spherical optical physics; Ferromagnetic materials; Spheres; Electric phase; Ferromagnetic spin; Fractional solutions; Heisenberg; Heisenberg ferromagnetic spin; Magnetic flow; Magnetic phasis; Spherical electric and magnetic flow density; Spherical frame; Spherical optical physic; Ferromagnetism